2001
DOI: 10.1046/j.1365-2109.2001.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Could a diet enriched with n-3 highly unsaturated fatty acids be considered a promising way to enhance the immune defences and the resistance ofPenaeidprawns to environmental stress?

Abstract: The prawn Penaeus stylirostris (Stimpson), when fed for 28 days with n-3 highly unsaturated fatty acid (HUFA)-enriched feed pellets, demonstrated an enhanced resistance to variations in environmental parameters (a decrease in temperature and salinity over a 4-day period from 28°C to 17°C and from 35½ to 10½ respectively) and an improvement in their immune defence potential, i.e. increased agglutination titre of plasma and increased respiratory burst of haemocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 16 publications
3
26
2
Order By: Relevance
“…All this confirms the superior ability of the animals fed n-3 HUFA enriched Artemia to cope with adverse environmental conditions. Similar to the present findings, Tackaert et al (1989) and Immanuel et al (2007) verified that P. monodon postlarvae fed n-3 HUFA enriched Artemia had higher survival when exposed to a range of salinity levels in comparison to postlarvae fed unenriched Artemia, while Chim et al (2001) demonstrated that feeding higher n-3 HUFA levels increased the cellular membrane Table 1. Mean values (± SE) of the main fatty acids (% area) in Artemia enriched with a commercial emulsion containing over 400 mg g-1 of n-3 highly unsaturated fatty acids (EG) and newly hatched Artemia nauplii (CG).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…All this confirms the superior ability of the animals fed n-3 HUFA enriched Artemia to cope with adverse environmental conditions. Similar to the present findings, Tackaert et al (1989) and Immanuel et al (2007) verified that P. monodon postlarvae fed n-3 HUFA enriched Artemia had higher survival when exposed to a range of salinity levels in comparison to postlarvae fed unenriched Artemia, while Chim et al (2001) demonstrated that feeding higher n-3 HUFA levels increased the cellular membrane Table 1. Mean values (± SE) of the main fatty acids (% area) in Artemia enriched with a commercial emulsion containing over 400 mg g-1 of n-3 highly unsaturated fatty acids (EG) and newly hatched Artemia nauplii (CG).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, shrimp fed n-3 HUFA rich diets have larger gill area , which concurs with the more ramified gill structure reported in n-3 HUFA fed P. monodon postlarvae (Rees et al, 1994). Although stress tests have been commonly used as a tool to compare the quality of crustacean larvae and juveniles in terms of tolerance to a number of physical and chemical parameters (Tackaert et al, 1989;Samocha et al, 1998;Cavalli et al, 2000;Chim et al, 2001;Álvarez et al, 2004;Martins et al, 2006;Immanuel et al, 2007;Sui et al, 2007), to date few studies have attempted to correlate the results of stress tests with the posterior growth performance of shrimp. In this regard, Bauman & Jamandre (1990) reported that batches of P. monodon postlarvae that responded positively to a salinity stress test presented a comparatively superior growout performance in ponds.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations